Brain imaging : case review series - Arora Ankur; Puri, Sunil K; Upreti Lalendra (New Delhi Jaypee Brothers Medical Publsihers, 2011)
Presentation of numerous different cases, covering major diseases radiologists mayy encounter on daily basis. Cases organised to mimic exam format, ideal for students preparing for MD, DMRD, DNB and FRCR examinations.
Keywords: Brain - Imaging - Case studies -- Brain -Imaging